Diet impacts on the biological aspects of pink bollworm, Pectinophora gossypiella (Lepidoptera: Gelechiidae) under controlled laboratory conditions - Arbab Ihsan (Public Library of Science (PLoS), 2021)
Background Pink bollworm, Pectinophora gossypiella (Lepidoptera: Gelechiidae) is a native pest of Asia and preferably invasion on cotton (Gossypium hirsutum L.) crop as a commendatory host plant. Commercially, G. hirsutum is known as white gold and is an important cash crop all over the globe. Limited studies were published to focus on certain dietary compositions against different cotton pests. Therefore, the present study was undertaken in the laboratory under controlled conditions (temperature: 27 ± 2°C and relative humidity: 60 ± 10%) to determine the impact of three different treatment diets (wheat germ meal, okra, and chickpea) on the biological aspects (lifetime, developmental period) of P. gossypiella. Results Results revealed that the shortest larval time of P. gossypiella was observed on the okra feed diet while the longest period was recorded on the wheat germ diet. Meanwhile, the pupation delay was noted on the wheat germ diet. The dietary influence was also observed on adult stages of female and male P. gossypiella (43.00 and 37.50 days respectively) and compared with a standard diet (56.50 and 52.50 days respectively). Furthermore, larval weighed more on the okra and chickpea diet followed by the wheat germ diet, whereas highest pupal weight was observed on the standard diet followed by the chickpea diet and okra diet. Conclusion Developmental parameters were significantly variant across all treatment diets, whereas the higher significant difference was reported on the okra diet. Therefore, the existing data of this study offers fruitful interventions for the future as a modified diet for large-scale and rapid mass production of P. gossypiella larvae.